Integrated Prognostic Significance of Serum S100B, Procalcitonin, and Neuron-Specific Enolase in Severe Traumatic Brain Injury: A Clinical Biochemistry Study: S100B, PCT, NSE in Severe TBI Prognosis - Kuang, Zhucai; Duan, Jingli; Pan, Changfu (Journal of Medical Biochemistry, 2026)
Background: Severe traumatic brain injury (sTBI) is associated with high mortality and long-term neurological disability. Reliable circulating biomarkers reflecting glial injury, neuronal damage, and systemic inflammatory activation may improve early prognostic stratification. This study evaluated the prognostic value of serum S100B protein, procalcitonin (PCT), and neuron-specific enolase (NSE) in patients with sTBI. Methods: A total of 103 patients with sTBI admitted between June 2021 and April 2025 were enrolled, together with 100 age-matched healthy controls. Peripheral venous blood was collected within 24 h after injury. Serum S100B was determined by enzyme-linked immunosorbent assay, PCT by chemiluminescent immunoassay, and NSE by electrochemiluminescence immunoassay. Functional outcome at 6 months was assessed using the Glasgow Outcome Scale (GOS). Patients were categorized into favorable prognosis (GOS 4–5) and poor prognosis (GOS 1–3) groups. Receiver operating characteristic (ROC) analysis was used to determine predictive performance. Results: Serum concentrations of S100B, PCT, and NSE were significantly elevated in patients with sTBI compared with healthy controls (all P<0.001). Patients with poor prognosis showed significantly higher levels of all three biomarkers than those with favorable prognosis (all P<0.001). ROC analysis demonstrated good prognostic discrimination for S100B (AUC=0.876), PCT (AUC=0.931), and NSE (AUC=0.981), while combined biomarker analysis yielded the highest predictive accuracy (AUC=0.996). Conclusions: Serum S100B, PCT, and NSE represent complementary biomarkers reflecting blood-brain barrier disruption, systemic inflammatory burden, and neuronal injury in sTBI. Their combined assessment provides excellent prognostic performance and may serve as a practical laboratory tool for early risk stratification and individualized clinical management.